The role of diabetes mellitus in the effectiveness of intradialytic exercise intervention on patients' muscle function - Kissova, Viera; Zelko, Aurel; Rosenberger, Jaroslav; Geckova, Andrea Madarasova (Endocrinología, diabetes y nutrición, 2022)
INTRODUCTION: The purpose of this study is to identify the role of diabetes mellitus in the effectiveness of intradialytic exercise intervention among haemodialysis patients. METHODS: In this multicentre study 90 dialysed patients were allocated to the experimental (EXG, n=57) or control group (CNG, n=33). In EXG, we included 20 diabetic and 37 non-diabetic patients. In CNG, we enrolled 8 diabetic and 25 non-diabetic patients. EXG underwent a 12-week supervised, progressive, intradialytic resistance training programme, while CNG stayed inactive during dialysis. Baseline, post-interventional and post-follow-up assessments of maximal force during hip extension (HE), hip flexion (HF) and knee extension (KE) contractions were completed in both groups of patients. RESULTS: HE increased in diabetic and non-diabetic EXG patients (diabetic EXG, change: +14.5N; 95% CI=-5.5 to +34.5; non-diabetic EXG, +18.6N; 95% CI=+3.4 to +33.8) and diabetic CNG patients (change: +17.9N; 95% CI=-9.2 to +44.9). Only non-diabetic CNG patients experienced a decrease in HE (change: -22.8N; 95% CI=-36.9 to -8.7, P<.05). CONCLUSIONS: Resistance training improved muscle function among dialysis patients regardless of the presence of diabetes mellitus. We found that non-diabetic patients lose their muscle function extensively during inactivity, while diabetic patients retain their muscle function.
Keywords: Kidney Failure, Chronic; terapie cvičením; svaly; Muscles; diabetes mellitus; Diabetes Mellitus; lidé; Renal Dialysis; chronické selhání ledvin; Exercise Therapy; dialýza ledvin; Humans